The Impact of Strategic Planning on Competitive Advantage in the Flour Industry - Lalwani, Keerti (ATLAS SkillTech University, 2025)
This report provides a comprehensive overview of my internship experience at a Flour Miller Group, where I was actively involved in multiple key departments, each contributing significantly to the company's operations and strategic direction. My primary focus was in the strategic department, where I played a crucial role in assisting the company with its Changing switching to a business-to-consumer (B2C) model from a business-to-business (B2B) one. This strategic shift was vital for the company as it sought to expand its market reach, establish a direct connection with consumers, and strengthen its brand presence in the retail sector. My responsibilities included not only developing strategies to facilitate this transition but also effectively communicating these strategies to management and employees to ensure alignment across the organization. In the finance department, I gained practical experience in managing the financial activities of the business, such as financial planning, budgeting, and cash flow management. I also learned about payroll processes, which are important in maintaining employee morale and ensuring business continuity.
Project Report on The Impact of Strategic Planning on Competitive Advantage in the Flour Industry (2023-2025) Under the Guidance of Prof. Chetana Asbe
Keywords: strategic shift; business-to-consumer (B2C); business-to-business (B2B)